Reflection on "the difference that difference makes". (2nd April 2016) - Jordan-Zachery, Julia S.
Abstract : Does difference make a difference? Does identity influence political behaviors? The simple answer is yes to both questions. Tripp's comparative analysis confirms that differences often do result in different approaches to raced-gendered responses to inequality and the quest for justice. This essay is intriguing for a number of reasons. However, I was left wondering if Tripp had flattened out differences in her attempt to make her larger point. As a result of the somewhat monolithic approach to understanding Black Diasporic political women, the overall analysis did not adequately explain how these women engage identity in strategic political decision-making. This leaves a number of questions. As I argue, integrating a relational approach into Tripp's analysis, might afford us an enhanced approach for explaining how these diverse women engage in prefigurtive and strategic politics.